Дидактические материалы по геометрии для 11 класса - Веселовский Сергей Борисович (Просвещение, 1992)
Экземпляры: КХ (20110420) / Инвентарный номер: 1005752 / Цена: 4.80 / Сис.шифр: 74.26 / Авт.знак: В 38 / ГРНТИ: 14 / ББК: 74.262.21